Electrostatic image developer, process cartridge, image forming device, and image forming method
By using titanium dioxide particles with different refractive index or microcrystalline diameters, fatty acid metal salt particles and abrasives in electrostatic image developer, the problem of uneven image concentration is solved, and the stability and charging performance during high-density image formation are achieved. promote.
Patent Information
- Application Number
- CN202010883167.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2020-08-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-08-28
AI Technical Summary
The conventional electrostatic image developer can easily lead to uneven image density when repeatedly forming high-density images, especially due to the reduction of charge exchangeability and widening of the charge distribution caused by the presence of titanium dioxide particles on the carrier surface.
Using two titanium dioxide particles with different refractive index or microcrystalline diameters, fatty acid metal salt particles and abrasives as external additives, the titanium dioxide particles are preferred and inhibited from being attached to the titanium dioxide particles through the electrostatic interaction and the action of the abrasives. The carrier surface is mixed and present to improve charging maintenance and prevent uneven image density.
The uneven image density during high-density image formation is effectively suppressed, and the charging characteristics and transfer performance of the image are improved.
Smart Images

Figure BDA0002654728460000231 
Figure BDA0002654728460000241 
Figure BDA0002654728460000301
Abstract
Description
Technical Field
[0001] The present invention relates to an electrostatic image developer, a process cartridge, an image forming apparatus, and an image forming method. Background Art
[0002] Japanese Patent Gazette No. 2005-266560 discloses "a toner for electrostatic latent image development, which is a toner for electrostatic latent image development comprising at least toner particles and external additives, characterized in that the external additives are two additives comprising a titanium compound A and a titanium compound B, the volume average particle size of the toner particles is 4 μm to 8 μm, and the GSD representing the volume particle size distribution is less than 1.23, and the shape factor SF1 is 110 to 14, and the powder resistivity and volume average particle size of the titanium compound A and the titanium compound B meet specified conditions."
[0003] In addition, Japanese Patent Application Laid-Open No. 2017-146538 discloses a toner for electrostatic image development, which satisfies the following conditions: "having toner particles, abrasive particles having two peaks in number particle size distribution, and fatty acid metal salt particles having one peak in number particle size distribution, wherein among the two peaks in the number particle size distribution of the abrasive particles, the particle size of the small diameter side peak is Da, the particle size of the large diameter side peak is Db, the particle size of one peak in the number particle size distribution of the fatty acid metal salt particles is Dc, and the volume average particle size of the toner particles is Dt, the following equations (1) to (3) are satisfied:
[0004] Formula (1): Da ≤ 0.5 × Dt
[0005] Formula (2): Dc ≦ 0.5 × Dt
[0006] ·Formula (3): Dt≦Db”.
[0007] In addition, Japanese Patent Gazette No. 2014-149503 discloses "an image forming device comprising: an image carrier for forming a latent image; a developing mechanism arranged relative to the surface of the image carrier in a non-contact state, and supplying a non-magnetic single-component developer containing crystalline polyester to the image carrier to develop the latent image; and a cleaning scraper in contact with the surface of the image carrier to clean the transfer residual developer on the surface of the image carrier, characterized in that the cleaning scraper is arranged at a position where gravity acts in a direction to prevent the following phenomenon: the transfer residual developer reaching the cleaning scraper due to the rotation of the image carrier enters the contact portion between the cleaning scraper and the surface of the image carrier." Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide an electrostatic image developer. Compared with an electrostatic image developer containing a toner including toner particles, a carrier and an external additive, in which the external additive is only two types of titanium dioxide particles with different refractive indices or crystallite diameters (crystallite diameters), the electrostatic image developer of the present invention can suppress the uneven image concentration caused by repeatedly forming high-density images.
[0009] According to a first aspect of the present invention, there is provided an electrostatic image developer comprising: a toner including toner particles; a carrier; and an external additive including two types of titanium dioxide particles having different refractive indices, fatty acid metal salt particles, and an abrasive.
[0010] According to the second embodiment of the present invention, the two types of titanium dioxide particles having different refractive indices are titanium dioxide particles (A) attached to the toner particles and titanium dioxide particles (B) attached to the carrier, and the refractive index of the titanium dioxide particles (A) is lower than that of the titanium dioxide particles (B).
[0011] According to a third aspect of the present invention, the refractive index of the titanium dioxide particles (A) is 2.0 or more and less than 2.4, and the refractive index of the titanium dioxide particles (B) is 2.4 or more and 2.8 or less.
[0012] According to a fourth aspect of the present invention, the fatty acid metal salt particles are fatty acid zinc particles, and the polishing agent is titanate metal salt particles.
[0013] According to a fifth aspect of the present invention, the fatty acid metal salt particles are zinc stearate particles, and the polishing agent is strontium titanate particles.
[0014] According to a sixth aspect of the present invention, the content of the fatty acid metal salt particles is 1% by mass or more and 10% by mass or less relative to the content of the titanium dioxide particles (A).
[0015] According to a seventh aspect of the present invention, the content of the polishing agent is 1% by mass or more and 10% by mass or less relative to the content of the titanium dioxide particles (A).
[0016] According to an eighth aspect of the present invention, the content of the titanium dioxide particles (A) is 0.1% by mass or more and 50% by mass or less relative to the content of the titanium dioxide particles (B).
[0017] According to a ninth aspect of the present invention, there is provided an electrostatic image developer comprising: a toner including toner particles; a carrier; and an external additive including two types of titanium dioxide particles having different crystallite diameters, fatty acid metal salt particles, and an abrasive.
[0018] According to a tenth aspect of the present invention, there is provided a process cartridge that is detachably mounted in an image forming apparatus and includes a developing mechanism that stores an electrostatic image developer and develops an electrostatic image formed on a surface of an image holding member into a toner image using the electrostatic image developer.
[0019] According to the 11th scheme of the present invention, there is provided an image forming device, which comprises: an image retaining body; a charging mechanism for charging the surface of the above-mentioned image retaining body; an electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the above-mentioned image retaining body; a developing mechanism for storing an electrostatic image developer and developing the electrostatic image formed on the surface of the above-mentioned image retaining body into a toner image using the above-mentioned electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the above-mentioned image retaining body to the surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the above-mentioned recording medium.
[0020] According to the 12th scheme of the present invention, an image forming method is provided, which has the following steps: a charging step of charging the surface of the image retainer; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image retainer; a developing step of developing the electrostatic image formed on the surface of the image retainer into a toner image using an electrostatic image developer; a transfer step of transferring the toner image formed on the surface of the image retainer to the surface of a recording medium; and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0021] Effects of the Invention
[0022] According to the above-mentioned scheme 1, 4, or 5, an electrostatic image developer is provided. Compared with an electrostatic image developer containing a toner including toner particles, a carrier and an external additive, in which the external additive is only two types of titanium dioxide particles with different refractive indices, the electrostatic image developer provided by the above scheme can suppress the uneven image concentration generated when a high-density image is repeatedly formed.
[0023] According to the above-mentioned second scheme, an electrostatic image developer is provided, in which the two titanium dioxide particles with different refractive indices are titanium dioxide particles (A) attached to the above-mentioned toner particles and titanium dioxide particles (B) attached to the above-mentioned carrier, and the refractive index of the above-mentioned titanium dioxide particles (A) is the same as the refractive index of the above-mentioned titanium dioxide particles (B) or higher than the refractive index of the above-mentioned titanium dioxide particles (B). Compared with the electrostatic image developer, the electrostatic image developer provided by this scheme can suppress the image concentration unevenness generated when repeatedly forming high-density images.
[0024] According to the above-mentioned third scheme, an electrostatic image developer is provided. Compared with the electrostatic image developer in which the refractive index of the above-mentioned titanium dioxide particles (A) is less than 2.0 or is greater than 2.4 or the refractive index of the above-mentioned titanium dioxide particles (B) is less than 2.4 or greater than 2.8, the electrostatic image developer provided by this scheme can suppress the uneven image concentration generated when repeatedly forming high-density images.
[0025] According to the above-mentioned scheme 6, an electrostatic image developer is provided. Compared with an electrostatic image developer in which the content of the above-mentioned fatty acid metal salt particles is less than 1 mass % or greater than 10 mass % relative to the content of the above-mentioned titanium dioxide particles (A), the electrostatic image developer provided by this scheme can suppress the uneven image concentration generated when repeatedly forming high-density images.
[0026] According to the above-mentioned scheme 7, an electrostatic image developer is provided. Compared with an electrostatic image developer in which the content of the above-mentioned abrasive is less than 1 mass % or greater than 10 mass % relative to the content of the above-mentioned titanium dioxide particles (A), the electrostatic image developer provided by this scheme can suppress the uneven image concentration generated when repeatedly forming high-density images.
[0027] According to the above-mentioned scheme 8, an electrostatic image developer is provided. Compared with an electrostatic image developer in which the content of the above-mentioned titanium dioxide particles (A) is less than 0.1 mass % or greater than 50 mass % relative to the content of the above-mentioned titanium dioxide particles (B), the electrostatic image developer provided by this scheme can suppress the uneven image concentration generated when repeatedly forming high-density images.
[0028] According to the above-mentioned scheme 9, an electrostatic image developer is provided. Compared with an electrostatic image developer containing a toner including toner particles, a carrier and an external additive, in which the external additive is only two types of titanium dioxide particles with different crystallite diameters, the electrostatic image developer provided by this scheme can suppress the uneven image concentration generated when high-density images are repeatedly formed.
[0029] According to the above-mentioned schemes 10 to 12, a processing box, an image forming device or an image forming method is provided. Compared with the case of using an electrostatic image developer containing a toner including toner particles, a carrier and an external additive wherein the external additive is only two types of titanium dioxide particles having different refractive indices or crystallite diameters, the processing box, image forming device or image forming method of the above scheme can suppress the uneven image concentration generated when repeatedly forming high-density images. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 1 is a schematic diagram showing the structure of the image forming apparatus according to the present embodiment.
[0031] Figure 21 is a schematic diagram showing the structure of the process cartridge according to the present embodiment. DETAILED DESCRIPTION
[0032] The present invention will be described in detail below by showing an embodiment as an example. These descriptions and examples are intended to illustrate the embodiment and are not intended to limit the scope of the embodiment.
[0033] In the numerical range recorded in stages among the present invention, the upper limit or lower limit recorded in a numerical range can be replaced by the upper limit or lower limit of the numerical range in other stages recorded. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit of this numerical range can be replaced by the value shown in the embodiment.
[0034] In the present specification, the term "step" includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step can be achieved.
[0035] Each component may contain two or more corresponding substances.
[0036] When referring to the amount of each component in a composition, if there are two or more substances corresponding to each component in the composition, unless otherwise stated, it refers to the total amount of the two or more substances present in the composition.
[0037] <Electrostatic Image Developer>
[0038] The electrostatic image developer according to the present embodiment contains a toner including toner particles, a carrier, and an external additive.
[0039] The external additives include two types of titanium dioxide particles having different refractive indices or crystallite diameters, fatty acid metal salt particles, and abrasives.
[0040] The electrostatic image developer of the present embodiment can suppress uneven image density caused by repeated high-density image formation due to the above-mentioned configuration. The reason for this is presumably as follows.
[0041] Conventionally, it is known that two kinds of titanium dioxide particles having different characteristics are added to toner to improve charging maintenance and transfer performance.
[0042] However, when printing at a high image density continuously, the two titanium dioxide particles migrate to the surface of the carrier, resulting in a negative polarity difference between the two titanium dioxide particles, and sometimes the conductive path is locally uneven, which may cause a local decrease in the charge exchangeability between the toner and the carrier, and further cause uneven image density with a wider charge distribution.
[0043] The electrostatic image developer of the present embodiment contains two types of titanium dioxide particles having different refractive indices or crystallite diameters, fatty acid metal salt particles, and abrasives as external additives.
[0044] By including two types of titanium dioxide particles having different refractive indices or crystallite diameters as an external additive, the charge retention performance is improved.
[0045] In addition, as an external additive, by including fatty acid metal salt particles, one of the above two titanium dioxide particles is preferentially attached to the fatty acid metal salt particles. As a result, on the carrier surface, the presence ratio of one of the above two titanium dioxide particles increases. That is, it is possible to suppress the reduction of local charge exchangeability caused by the uneven resistance of the carrier surface due to the mixed presence of two titanium dioxide particles on the carrier surface. Here, it is presumed that the preferential attachment of one titanium dioxide particle to the fatty acid metal salt particle is due to the electrostatic interaction between the fatty acid metal salt particles and the titanium dioxide particles.
[0046] Furthermore, even when the two types of titanium dioxide particles migrate to the surface of the carrier, by including a polishing agent as an external additive, the surface of the carrier can be polished to remove the portion where the two types of titanium dioxide particles are mixed.
[0047] From this, it is inferred that in the electrostatic image developer of the present embodiment, even when high-density images are repeatedly formed, the two types of titanium dioxide particles are suppressed from being mixed on the carrier surface, and image density unevenness is also suppressed.
[0048] (Toner)
[0049] The toner contains toner particles.
[0050] The toner particles are constituted by, for example, containing a binding resin and, if necessary, a colorant, a release agent, and other additives.
[0051] - Adhesive resin -
[0052] As the adhesive resin, for example, there can be mentioned a vinyl resin formed by a homopolymer of the following monomers or a copolymer of two or more of these monomers, the monomers being: styrenes (for example, styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (for example, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (for example, acrylonitrile, methacrylonitrile, etc.), vinyl ethers (for example, vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (for example, ethylene, propylene, butadiene, etc.), etc.
[0053] Examples of the adhesive resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosins, mixtures of these resins with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these resins.
[0054] These adhesive resins may be used alone or in combination of two or more.
[0055] As the adhesive resin, a polyester resin is suitable.
[0056] Examples of the polyester resin include known polyester resins.
[0057] Examples of the polyester resin include polycondensates of polycarboxylic acids and polyols. As the polyester resin, a commercially available product may be used, or a synthetic product may be used.
[0058] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), and their anhydrides or their lower (e.g., carbon number 1 to 5) alkyl esters. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.
[0059] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a crosslinked structure or a branched structure may be used in combination. Examples of trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0060] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0061] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.
[0062] As the polyol, a diol may be used in combination with a trivalent or higher polyol having a crosslinked structure or a branched structure. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.
[0063] The polyols may be used alone or in combination of two or more.
[0064] The glass transition temperature (Tg) of the polyester resin is preferably 50°C to 80°C, more preferably 50°C to 65°C.
[0065] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for measuring glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics".
[0066] The weight average molecular weight (Mw) of the polyester resin is preferably 5,000 to 1,000,000, and more preferably 7,000 to 500,000.
[0067] The number average molecular weight (Mn) of the polyester resin is preferably 2,000 or more and 100,000 or less.
[0068] The molecular weight distribution Mw / Mn of the polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.
[0069] It should be noted that the weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement using GPC, a Tosoh GPC HLC-8120GPC is used as a measuring device, a Tosoh column TSK gel Super HM-M (15 cm) is used, and the measurement is performed using a THF solvent. The weight average molecular weight and the number average molecular weight are calculated based on the measurement results using a molecular weight calibration curve made from a monodisperse polystyrene standard sample.
[0070] The polyester resin is obtained by a known production method. Specifically, for example, the polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water or alcohol generated during condensation.
[0071] It should be noted that, when the raw material monomer is insoluble or incompatible at the reaction temperature, a high boiling point solvent may be added as a dissolution aid to dissolve it. In this case, the polycondensation reaction is carried out while the dissolution aid is removed by distillation. In the case of monomers with poor compatibility, the monomers with poor compatibility may be condensed in advance with a specific acid or alcohol to be polycondensed with the monomers, and then polycondensed with the main component.
[0072] The content of the binder resin is, for example, preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and further preferably 60% by mass to 85% by mass, based on the entire toner particles.
[0073] -Colorants-
[0074] Examples of the colorant include various pigments such as carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, sulfur-resistant orange, Vochug red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose red, aniline blue, ultramarine blue, oil-soluble blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based.
[0075] The coloring agent may be used alone or in combination of two or more.
[0076] The colorant may be a colorant that has been subjected to surface treatment as required, or may be used in combination with a dispersant. In addition, two or more colorants may be used in combination.
[0077] The content of the colorant is, for example, preferably from 1 mass % to 30 mass % both inclusive, and more preferably from 3 mass % to 15 mass % both inclusive, based on the entire toner particles.
[0078] -Release agent-
[0079] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral and petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.
[0080] The melting temperature of the release agent is preferably 50°C to 110°C, more preferably 60°C to 100°C.
[0081] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) according to the “melting peak temperature” described in the method for measuring melting temperature in JIS K 7121-1987 “Method for measuring transition temperatures of plastics”.
[0082] The content of the release agent is, for example, preferably from 1 mass % to 20 mass % both inclusive, and more preferably from 5 mass % to 15 mass % both inclusive, based on the entire toner particles.
[0083] -Other additives-
[0084] Examples of other additives include known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.
[0085] -Characteristics of toner particles, etc.-
[0086] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that covers the core portion.
[0087] Here, the toner particles of the core-shell structure may be composed of, for example, a core portion including a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer including a binder resin.
[0088] The volume average particle diameter (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0089] Incidentally, various average particle diameters and various particle size distribution indices of the toner particles were measured using Coulter Multisizer II (manufactured by Beckman Coulter) and the electrolyte was measured using ISOTON-II (manufactured by Beckman Coulter).
[0090] In the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and then added to 100 ml to 150 ml of the electrolyte.
[0091] The electrolyte in which the sample was suspended was dispersed by an ultrasonic disperser for 1 minute, and the particle size distribution of particles with a particle size of 2 μm to 60 μm was measured by Coulter Multisizer II using an aperture of 100 μm. The number of particles sampled was 50,000.
[0092] For the particle size range (segment) divided based on the measured particle size distribution, the volume and number of particles are plotted as cumulative distributions starting from the small diameter side, the particle size at the cumulative 16% point is defined as the volume particle size D16v and the number particle size D16p, the particle size at the cumulative 50% point is defined as the volume average particle size D50v and the cumulative number average particle size D50p, and the particle size at the cumulative 84% point is defined as the volume particle size D84v and the number particle size D84p.
[0093] Using these values, the volume particle size distribution index (GSDv) is calculated as (D84v / D16v) 1 / 2 Calculate and convert the particle size distribution index (GSDp) into (D84p / D16p) 1 / 2 Calculated.
[0094] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0095] The average circularity of the toner particles is determined by (equivalent circular circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.
[0096] First, the toner particles to be measured are collected by suction and formed into a flat flow, and the particles are momentarily strobed to obtain a particle image as a still image, and the particle image is analyzed by a flow particle image analyzer (FPIA-3000 manufactured by Sysmex) to obtain the average circularity. The number of samples for obtaining the average circularity is set to 3500.
[0097] In addition, when the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then subjected to ultrasonic treatment to obtain toner particles from which the external additive is removed.
[0098] (Carrier)
[0099] The carrier is not particularly limited, and any known carrier may be used. Examples of the carrier include: a coated carrier in which a core material formed of magnetic powder is coated with a resin; a magnetic powder dispersed carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated carrier in which porous magnetic powder is impregnated with a resin; and the like.
[0100] Note that the magnetic powder dispersed carrier and the resin impregnated carrier may be carriers in which the constituent particles of the carrier are used as core materials and the core materials are coated with a coating resin.
[0101] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; and magnetic oxides such as ferrite and magnetite.
[0102] Examples of the coating resin and base resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, pure silicone resin containing an organic siloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenol resin, epoxy resin, and the like.
[0103] It should be noted that the coating resin and the base resin may contain other additives such as conductive particles.
[0104] Examples of the conductive particles include particles of metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0105] Here, when the coating resin is coated on the core surface, a coating layer forming solution obtained by dissolving the coating resin and various additives as necessary in an appropriate solvent can be used for coating. The solvent is not particularly limited and can be selected by considering the coating resin used, coating suitability, etc.
[0106] Specific resin coating methods include: an immersion method, in which the core material is immersed in a coating layer forming solution; a spray method, in which the coating layer forming solution is sprayed onto the surface of the core material; a fluidized bed method, in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coater method, in which the core material of the carrier is mixed with the coating layer forming solution in a kneading coater and then the solvent is removed; and the like.
[0107] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, more preferably 3:100 to 20:100.
[0108] (External Additives)
[0109] The external additives include two kinds of titanium dioxide particles having different refractive indices or crystallite diameters, fatty acid metal salt particles and abrasives.
[0110] -Titanium dioxide particles-
[0111] As the titanium dioxide particles, two types of titanium dioxide particles having different refractive indices or crystallite diameters are used.
[0112] In addition, the surface of the titanium dioxide particles can be subjected to hydrophobic treatment. Hydrophobic treatment is carried out by, for example, immersing the titanium dioxide particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, silane coupling agents, silicone oils, titanate coupling agents, aluminum coupling agents, etc. can be cited. These treatment agents can be used alone or in combination of two or more.
[0113] The amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the titanium dioxide particles.
[0114] The number average particle size of the titanium dioxide particles is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.02 μm or more and 5 μm or less.
[0115] Regarding the number average particle size of titanium dioxide particles, a toner to which an external additive containing titanium dioxide particles is added is imaged using a scanning electron microscope (SEM) (manufactured by Hitachi High-Technologies Co., Ltd., S-4700) at a magnification of 40,000 times, and observed at an accelerating voltage of 15 kV, an emission current of 20 μA, and a WD of 15 mm. Specific silicon dioxide particles are analyzed using image processing and analysis software WinRoof (manufactured by Mitani Shoji Co., Ltd.) to obtain an equivalent circle diameter, and the particle diameter (equivalent circle diameter) is measured for at least 100 particles to obtain a number average particle diameter, which is a particle diameter at which 50% of the points are accumulated from the smaller diameter side in a distribution based on the number of particle diameters.
[0116] In the image analysis for determining the equivalent circle diameter of 100 titanium dioxide particles as the measurement object, an analysis device (ERA-8900: manufactured by Elionix) was used to capture a two-dimensional image with a magnification of 10,000 times, and the image analysis software WinROOF (manufactured by Mitani Shoji Co., Ltd.) was used to determine the projection area under the condition of 0.010000 μm / pixel. The equivalent circle diameter was determined using the formula: equivalent circle diameter = 2√(projection area / π).
[0117] From the perspective of suppressing uneven image density, it is preferred that the two titanium dioxide particles with different refractive indices are titanium dioxide particles (A) attached to the above-mentioned toner particles and titanium dioxide particles (B) attached to the above-mentioned carrier, and the refractive index of the above-mentioned titanium dioxide particles (A) is lower than the refractive index of the above-mentioned titanium dioxide particles (B).
[0118] The reason why unevenness in image density is suppressed by setting the refractive index of the titanium dioxide particles (A) and the titanium dioxide particles (B) to the above-mentioned configuration is presumed to be as follows.
[0119] It is presumed that the titanium dioxide particles (A) having a low refractive index tend to have a higher negative polarity than the titanium dioxide particles (B) having a high refractive index. Furthermore, by attaching the titanium dioxide particles (B) to the carrier and attaching the titanium dioxide particles (A) to the toner surface, a suitable potential difference is generated between the toner and the carrier, thereby improving the charging characteristics.
[0120] In addition, the fatty acid metal salt particles included as an external additive have positive polarity. Therefore, the fatty acid metal salt particles preferentially adhere to the titanium dioxide particles (A) with high negative polarity through electrostatic interaction. As a result, the mixed presence of the titanium dioxide particles (A) and the titanium dioxide particles (B) on the surface of the carrier is suppressed. In addition, even if the titanium dioxide particles (A) and the titanium dioxide particles (B) are mixed on the surface of the carrier, grinding can be performed by the abrasive included as an external additive.
[0121] That is, it is possible to further suppress a decrease in local charge exchangeability due to the mixed presence of two types of titanium dioxide particles on the surface of the support.
[0122] Therefore, it is estimated that image density unevenness is suppressed.
[0123] From the viewpoint of suppressing uneven image density, the difference in refractive index between the titanium dioxide particles (A) and titanium dioxide (B) is preferably 0.1 to 0.8, more preferably 0.2 to 0.6, and even more preferably 0.2 to 0.4.
[0124] The refractive index of the titanium dioxide particles (A) is preferably 2.0 or more and less than 2.4, more preferably 2.1 or more and less than 2.4, and further preferably 2.2 or more and less than 2.4.
[0125] The refractive index of the titanium dioxide particles (B) is preferably 2.4 to 2.8, more preferably 2.6 to 2.8, and even more preferably 2.6 to 2.7.
[0126] When the refractive index of the titanium dioxide particles (A) is 2.0 or more, it is easy to suppress the overcharging of the toner, which is preferred.
[0127] When the refractive index of the titanium dioxide particles (A) is less than 2.4, the toner can easily achieve a charging potential required for development, which is preferred.
[0128] Furthermore, when the refractive index of the titanium dioxide particles (A) is 2.0 or more and less than 2.4, unevenness in image density is suppressed, which is preferred.
[0129] When the refractive index of the titanium dioxide particles (B) is 2.4 or more, it is easy to suppress the overcharging of the toner, which is preferred.
[0130] When the refractive index of the titanium dioxide particles (B) is 2.8 or less, the toner can easily achieve a charging potential required for development, which is preferred.
[0131] Furthermore, when the refractive index of the titanium dioxide particles (B) is 2.4 or more and 2.8 or less, unevenness in image density is suppressed, which is preferred.
[0132] Regarding the measurement of the refractive index of titanium dioxide particles, firstly, the toner or developer is subjected to ultrasonic treatment, and the resulting external additive is separated using a centrifugal separator to separate the titanium dioxide particles with a high specific gravity. The refractive index of the resulting titanium dioxide particles is measured using the measurement method described in JIS K7142 (2014), for example.
[0133] Preferably, the two types of titanium dioxide particles having different crystallite diameters are titanium dioxide particles (A) attached to the toner particles and titanium dioxide particles (B) attached to the carrier, and the crystallite diameter of the titanium dioxide particles (B) is larger than that of the titanium dioxide particles (A).
[0134] The reason why unevenness in image density is suppressed by setting the crystallite diameters of the titanium dioxide particles (A) and the titanium dioxide particles (B) to the above-mentioned values is presumed to be as follows.
[0135] It is speculated that titanium dioxide particles (B) having a large crystallite diameter tend to have high conductivity and low chargeability compared to titanium dioxide particles (A) having a small crystallite diameter. Furthermore, by attaching titanium dioxide particles (B) to the carrier and titanium dioxide particles (A) to the toner surface, a moderate potential difference is generated between the toner and the carrier, thereby improving the chargeability.
[0136] In addition, the fatty acid metal salt particles included as an external additive have positive polarity. Therefore, the fatty acid metal salt particles preferentially adhere to the titanium dioxide particles (B) with high conductivity and low chargeability through electrostatic interaction. As a result, the migration of the titanium dioxide particles (B) to the carrier surface is suppressed. In addition, even if the titanium dioxide particles (B) migrate to the carrier surface, they will be ground by the abrasive included as an external additive, so the proportion of titanium dioxide particles (A) on the carrier surface increases.
[0137] That is, it is possible to further suppress a decrease in local charge exchangeability due to the mixed presence of two types of titanium dioxide particles on the surface of the support.
[0138] It is therefore presumed that unevenness in image density is suppressed.
[0139] From the perspective of suppressing uneven image density, the difference (absolute value) in crystallite diameter between titanium dioxide particles (A) and titanium dioxide (B) is preferably 24 nm to 32 nm, more preferably 25 nm to 31 nm, and even more preferably 26 nm to 30 nm.
[0140] The crystallite diameter of the titanium dioxide particles (A) is preferably 12 nm or more and less than 16 nm, more preferably 13 nm or more and less than 15 nm, further preferably 14 nm or more and less than 15 nm.
[0141] The crystallite diameter of the titanium dioxide particles (B) is preferably 40 nm to 44 nm, more preferably 41 nm to 43 nm, and even more preferably 42 nm to 43 nm.
[0142] When the crystallite diameter of the titanium dioxide particles (A) is 12 nm or more, it is easy to suppress the charging of the toner, which is preferred.
[0143] When the crystallite diameter of the titanium dioxide particles (A) is less than 16 nm, the toner can easily achieve a charge potential required for development, which is preferred.
[0144] Furthermore, when the crystallite diameter of the titanium dioxide particles (A) is 12 nm or more and less than 16 nm, unevenness in image density is suppressed, which is preferred.
[0145] When the crystallite diameter of the titanium dioxide particles (B) is 40 nm or more, it is easy to suppress the charging of the toner, which is preferred.
[0146] When the crystallite diameter of the titanium dioxide particles (B) is 44 nm or less, the toner can easily achieve a charge potential required for development, which is preferred.
[0147] Furthermore, when the crystallite diameter of the titanium dioxide particles (B) is 40 nm or more and 44 nm or less, unevenness in image density is suppressed, which is preferred.
[0148] The "fine crystal (crystal)" in the present embodiment refers to each single crystal constituting a polycrystalline body or a single crystal observed in an amorphous body.
[0149] In addition, the "crystallite diameter" in the present embodiment means the average diameter of the crystallites which are the minimum units constituting the crystal body.
[0150] The method for measuring the crystallite diameter of the titanium oxide particles in the present embodiment is as follows.
[0151] The crystallite diameter in this embodiment is determined as follows.
[0152] The target crystal is measured using an X-ray diffractometer, and the crystallite diameter is determined from the following Scherrer equation.
[0153] D=K×λ / (β×cosθ)
[0154] D: crystallite diameter (nm),
[0155] K: Scherrer constant,
[0156] λ: X-ray wavelength,
[0157] β: Width of the diffraction line (extended),
[0158] θ: diffraction angle (2θ / θ)
[0159] It is preferred that the crystal structure of the titanium dioxide particles (A) is anatase type, and the crystal structure of the titanium dioxide particles (B) is rutile type.
[0160] From the perspective of suppressing uneven image concentration, the content of titanium dioxide particles (A) relative to the content of titanium dioxide particles (B) is preferably 0.1 mass % to 50 mass %, more preferably 0.1 mass % to 25 mass %, further preferably 0.4 mass % to 1 mass %, and most preferably 0.5 mass % to 0.6 mass %.
[0161] The total content of the titanium dioxide particles (A) and the titanium dioxide particles (B) is preferably 0.1% by mass to 0.8% by mass, more preferably 0.2% by mass to 0.6% by mass, and even more preferably 0.2% by mass to 0.4% by mass, based on the total mass of the electrostatic image developer.
[0162] -Fatty acid metal salt particles-
[0163] The fatty acid metal salt particles are particles of a salt formed of a fatty acid and a metal and have positive chargeability.
[0164] The fatty acid may be any of a saturated fatty acid or an unsaturated fatty acid. Examples of the fatty acid include fatty acids having a carbon number of 10 to 25 (preferably 12 to 22). It should be noted that the carbon number of the fatty acid includes the carbon of the carboxyl group.
[0165] Examples of fatty acids include saturated fatty acids such as behenic acid, stearic acid, palmitic acid, myristic acid, and lauric acid, and unsaturated fatty acids such as oleic acid, linoleic acid, and ricinoleic acid. Among these fatty acids, stearic acid and lauric acid are preferred from the perspective of suppressing uneven image density, and stearic acid is more preferred.
[0166] The metal may be a divalent metal. Examples of the metal include magnesium, calcium, aluminum, barium, and zinc. Among these, zinc is preferred from the perspective of suppressing uneven image density.
[0167] Examples of fatty acid metal salt particles include metal salts of stearic acid such as aluminum stearate, calcium stearate, potassium stearate, magnesium stearate, barium stearate, lithium stearate, zinc stearate, copper stearate, lead stearate, nickel stearate, strontium stearate, cobalt stearate, and sodium stearate; metal salts of palmitic acid such as zinc palmitate, cobalt palmitate, copper palmitate, magnesium palmitate, aluminum palmitate, and calcium palmitate; metal salts of lauric acid such as zinc laurate, manganese laurate, calcium laurate, iron laurate, magnesium laurate, and aluminum laurate; metal salts of oleic acid such as zinc oleate, manganese oleate, iron oleate, aluminum oleate, copper oleate, magnesium oleate, and calcium oleate; metal salts of linoleic acid such as zinc linoleate, cobalt linoleate, and calcium linoleate; and metal salts of ricinoleic acid such as zinc ricinoleate and aluminum ricinoleate.
[0168] Among these, from the viewpoint of suppressing uneven image density, the fatty acid metal salt particles are preferably fatty acid zinc particles, more preferably zinc stearate particles or zinc laurate particles, and still more preferably zinc stearate particles.
[0169] The method for producing the fatty acid metal salt particles is not particularly limited, and examples thereof include a method of replacing a fatty acid alkali metal salt with cations, a method of directly reacting a fatty acid with a metal hydroxide, and the like.
[0170] As an example of a method for producing zinc stearate particles as fatty acid metal salt particles, for example, there are a method of replacing cations of sodium stearate, a method of reacting stearic acid with zinc hydroxide, and the like.
[0171] The number average particle size of the fatty acid metal salt particles is preferably from 0.5 μm to 3.0 μm, and more preferably from 1.0 μm to 2.5 μm.
[0172] The number average particle size of the fatty acid metal salt particles is a value measured by the following method.
[0173] A surfactant is added to water whose specific gravity is adjusted to 1.5 or more and 2.0 or less by dissolving potassium iodide or the like, and a developer is dispersed in the resulting aqueous solution. The dispersion is then left for 24 hours, so that toner particles and fatty acid metal salt particles having a specific gravity lighter than the aqueous solution are separated to the upper part of the aqueous solution, and carrier, titanium dioxide particles, and abrasive having a specific gravity heavier than the aqueous solution are precipitated to the lower part of the aqueous solution. The toner particles and fatty acid metal salt particles separated to the upper part of the aqueous solution are collected, the collected solution is dried at room temperature (25° C.), and the resulting sample is observed by SEM, and particles having a particle size of 0.1 μm or more other than the toner particles are regarded as fatty acid metal salt particles.
[0174] Then, the equivalent circle diameter of each of the 100 fatty acid metal salt particles to be measured is determined by image analysis, and the equivalent circle diameter at the point where the number of particles accumulated from the smaller diameter side in the number-based distribution is 50% (50th) is taken as the number average particle diameter.
[0175] In the image analysis for determining the equivalent circle diameter of 100 fatty acid metal salt particles as the measurement object, an analysis device (ERA-8900: manufactured by Elionix) was used to capture a two-dimensional image with a magnification of 10,000 times, and the image analysis software WinROOF (manufactured by Mitani Shoji Co., Ltd.) was used to determine the projected area under the condition of 0.010000 μm / pixel. The equivalent circle diameter was determined by the formula: equivalent circle diameter = 2√(projected area / π).
[0176] When fatty acid metal salt particles are separately obtained or collected from a developer, the above-mentioned measurement is performed using the obtained or collected fatty acid metal salt particles as the measurement object.
[0177] From the perspective of suppressing uneven image density, the content of the fatty acid metal salt particles is preferably 1 mass % to 10 mass % relative to the content of the titanium dioxide particles (B), more preferably 2 mass % to 9 mass %, and even more preferably 3 mass % to 8 mass %.
[0178] When the content of the fatty acid metal salt particles is 1% by mass or more relative to the content of the titanium dioxide particles (B), migration of the titanium dioxide particles (B) to the surface of the support is suppressed, which is preferred.
[0179] When the content of the fatty acid metal salt particles is 10% by mass or less based on the content of the titanium dioxide particles (B), the toner can easily achieve a charging potential required for development, which is preferred.
[0180] The content of the fatty acid metal salt particles is preferably 0.01% by mass to 0.5% by mass, more preferably 0.02% by mass to 0.1% by mass, and further preferably 0.03% by mass to 0.06% by mass, based on the toner particles.
[0181] - Abrasives -
[0182] The abrasive is not particularly limited, and examples thereof include metal oxides other than titanium dioxide and silicon dioxide, such as cerium oxide, magnesium oxide, aluminum oxide (aluminum oxide), zinc oxide, and zirconium oxide; carbides such as silicon carbide; nitrides such as boron nitride; pyrophosphates such as calcium pyrophosphate particles; carbonates such as calcium carbonate and barium carbonate; metal titanate particles such as barium titanate, magnesium titanate, calcium titanate, and strontium titanate; and other inorganic particles. The abrasive may be used alone or in combination of two or more. Among these, metal titanate particles, more preferably strontium titanate particles, are preferred as the abrasive in terms of suppressing uneven image density.
[0183] Abrasives can utilize, for example, a hydrophobizing treatment agent to apply hydrophobizing treatment to the surface. As a hydrophobizing treatment agent, for example, known organosilicon compounds with alkyl groups (such as methyl, ethyl, propyl, butyl, etc.) can be cited, and specific examples such as silazane compounds (such as silane compounds such as methyltrimethoxysilane, dimethyldimethoxysilane, trimethylchlorosilane, trimethylmethoxysilane, hexamethyldisilazane, tetramethyldisilazane, etc.) can be cited. The hydrophobizing treatment agent can be used alone or in combination with two or more.
[0184] From the viewpoint of suppressing uneven image density, the number average particle size of the polishing agent is preferably 0.5 μm to 5.0 μm, more preferably 0.5 μm to 3.0 μm, and even more preferably 0.5 μm to 2.0 μm.
[0185] The number average particle size of the polishing agent is a value measured by the following method.
[0186] A surfactant is added to water whose specific gravity is adjusted to 1.5 or more and 2.0 or less by dissolving potassium iodide or the like, and a developer is dispersed in the resulting aqueous solution. The dispersion is then left for 24 hours, so that toner particles and fatty acid metal salt particles having a specific gravity lighter than the aqueous solution are separated to the upper part of the aqueous solution, and carriers, titanium dioxide particles, and abrasives having a specific gravity heavier than the aqueous solution are precipitated to the lower part of the aqueous solution. The carriers, titanium dioxide particles, and abrasives precipitated to the lower part of the aqueous solution are collected, the collected solution is dried at room temperature (25° C.), and the obtained sample is observed by SEM, and particles having a particle size of 0.1 μm or more other than the carrier and titanium dioxide particles are used as abrasives.
[0187] Then, the equivalent circle diameter of each of the 100 abrasives to be measured was determined by image analysis, and the equivalent circle diameter at the point where the number of particles accumulated 50% (the 50th point) from the smaller diameter side in the number-based distribution was taken as the number average particle size.
[0188] In the image analysis for determining the equivalent circle diameters of 100 abrasives to be measured, an analysis device (ERA-8900: manufactured by Elionix) was used to capture a two-dimensional image at a magnification of 10,000 times, and the image analysis software WinROOF (manufactured by Mitani Shoji Co., Ltd.) was used to determine the projection area under the condition of 0.010000 μm / pixel. The equivalent circle diameter was determined by the formula: equivalent circle diameter = 2√(projection area / π).
[0189] In addition, when the abrasive is obtained separately or collected from the developer, the above-mentioned measurement is performed using the obtained or collected abrasive as the measurement object.
[0190] The content of the abrasive relative to the content of the titanium dioxide particles (A) is preferably 1% by mass to 10% by mass, more preferably 2% by mass to 9% by mass, and even more preferably 3% by mass to 7% by mass.
[0191] When the content of the polishing agent is 1 mass % or more relative to the content of the titanium dioxide particles (A), the mixed existence of the two types of titanium dioxide particles on the surface of the carrier is suppressed, which is preferred.
[0192] When the content of the abrasive is 10% by mass or less based on the content of the titanium dioxide particles (A), the toner can easily achieve a charging level required for development, which is preferred.
[0193] The content of the abrasive is preferably 0.0001% by mass to 0.005% by mass, more preferably 0.0002% by mass to 0.001% by mass, and further preferably 0.0003% by mass to 0.0006% by mass, based on the total mass of the electrostatic image developer.
[0194] -Other additives-
[0195] As the external additive, other external additives than the titanium dioxide particles, the fatty acid metal salt particles and the abrasive may be contained.
[0196] As other external additives, for example, inorganic particles having a number average particle size of 1 μm or less (preferably 500 nm or less) (hereinafter also referred to as "small diameter inorganic particles") can be cited. It should be noted that the number average particle size of the small diameter inorganic particles is a value measured by the same method as the number average particle size of the abrasive particles.
[0197] Examples of small-diameter inorganic particles include SiO2 , CuO, SnO 2 , Fe 2 O 3 ,BaO,CaO,K 2 O、Na 2 O、CaO·SiO 2 , K 2 O·(TiO 2 )n、Al 2 O 3 ·2SiO 2 MgCO 3 ,BaSO 4 MgSO 4 wait.
[0198] As other external additives, the surface of the small-diameter inorganic particles is suitably subjected to hydrophobization. The hydrophobization is carried out by, for example, immersing the inorganic particles in a hydrophobization treatment agent. The hydrophobization treatment agent is not particularly limited, and for example, silane coupling agents, silicone oils, titanate coupling agents, aluminum coupling agents, etc. can be cited. These can be used alone or in combination of two or more.
[0199] The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the small-diameter inorganic particles.
[0200] Other examples of the external additives include resin particles (resin particles such as polythrene, polymethyl methacrylate (PMMA), and melamine resin), detergent active agents (for example, particles of fluorine-based high molecular weight bodies), and the like.
[0201] The amount of other external additives added is, for example, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0202] <Image Forming Apparatus / Image Forming Method>
[0203] The image forming apparatus and image forming method according to the present embodiment will be described.
[0204] The image forming device of the present embodiment comprises: an image holder; a charging mechanism for charging the surface of the image holder; an electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holder; a developing mechanism for storing an electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer of the present embodiment is used as the electrostatic image developer.
[0205] An image forming method (image forming method of the present embodiment) is implemented using the image forming device of the present embodiment, and the method has the following steps: a charging step of charging the surface of the image retaining body; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image retaining body; a developing step of developing the electrostatic image formed on the surface of the image retaining body into a toner image using the electrostatic image developer of the present embodiment; a transfer step of transferring the toner image formed on the surface of the image retaining body to the surface of the recording medium; and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0206] The image forming device of this embodiment is applicable to the following well-known image forming devices: a device using a direct transfer method for directly transferring a toner image formed on the surface of an image holder to a recording medium; a device using an intermediate transfer method for transferring a toner image formed on the surface of an image holder to the surface of an intermediate transfer body for the first time, and transferring the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium for a second time; a device having a cleaning mechanism for cleaning the surface of the image holder after the toner image is transferred and before charging; a device having a static elimination mechanism for eliminating static by irradiating the surface of the image holder with static elimination light after the toner image is transferred and before charging; and the like.
[0207] In the case of an intermediate transfer device, the transfer mechanism used is, for example, a structure having the following components: an intermediate transfer body to the surface of which the toner image is transferred; a primary transfer mechanism that transfers the toner image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the first time; and a secondary transfer mechanism that transfers the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium for the second time.
[0208] It should be noted that, in the image forming apparatus of the present embodiment, the portion including the developing mechanism may be a cartridge structure (processing cartridge) that is loaded and unloaded in the image forming apparatus. As the processing cartridge, for example, a processing cartridge having a developing mechanism storing the electrostatic image developer of the present embodiment is suitable.
[0209] An example of the image forming apparatus according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the other descriptions are omitted.
[0210] Figure 1 2 is a diagram schematically showing the structure of the image forming apparatus according to the present embodiment.
[0211] Figure 1The image forming apparatus shown in the figure has the first to fourth image forming units 10Y, 10M, 10C, 10K (image forming mechanism) of the electronic photography method, and the first to fourth image forming units 10Y, 10M, 10C, 10K (image forming mechanism) output respective color images of yellow (Y), magenta (M), cyan (C), and black (K) based on color separation image data. These image forming units (hereinafter sometimes referred to as "units") 10Y, 10M, 10C, 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. It should be noted that these units 10Y, 10M, 10C, 10K may be process cartridges that are loaded and unloaded in the image forming apparatus.
[0212] Above the drawing of each unit 10Y, 10M, 10C, 10K, an intermediate transfer belt 20 as an intermediate transfer body is extended through each unit. The intermediate transfer belt 20 is wound around a driving roller 22 and a support roller 24 that are arranged separately from each other in the direction from left to right in the figure, and is connected to the inner surface of the intermediate transfer belt 20, so that it runs in the direction from the first unit 10Y to the fourth unit 10K. It should be noted that the support roller 24 is applied with a force in a direction away from the driving roller 22 by a spring not shown in the figure, and tension is applied to the intermediate transfer belt 20 wound on the two. In addition, an intermediate transfer body cleaning device 30 is provided on the image holding body side of the intermediate transfer belt 20, which is opposite to the driving roller 22.
[0213] In addition, toner is supplied to the developing devices (developing mechanisms) 4Y, 4M, 4C, 4K of each unit 10Y, 10M, 10C, 10K, respectively. The toner is a toner containing four colors of yellow, magenta, cyan, and black stored in the toner boxes 8Y, 8M, 8C, 8K.
[0214] The first to fourth units 10Y, 10M, 10C, and 10K have the same structure and operation, and therefore, the first unit 10Y disposed on the upstream side of the intermediate transfer belt running direction for forming a yellow image is described as a representative. It should be noted that the same parts as the first unit 10Y are marked with reference numerals with magenta (M), cyan (C), and black (K) instead of yellow (Y), and the description of the second to fourth units 10M, 10C, and 10K is omitted.
[0215] The first unit 10Y has a photoreceptor 1Y that functions as an image holder. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging mechanism) 2Y that charges the surface of the photoreceptor 1Y to a preset potential; an exposure device (an example of an electrostatic image forming mechanism) 3 that forms an electrostatic image by exposing the charged surface using a laser beam 3Y based on a color separation image signal; a developing device (an example of a developing mechanism) 4Y that supplies the charged toner to the electrostatic image to develop the electrostatic image; a primary transfer roller 5Y (an example of a primary transfer mechanism) that transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning mechanism) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.
[0216] It should be noted that the primary transfer roller 5Y is arranged inside the intermediate transfer belt 20 and is provided at a position opposite to the photoreceptor 1Y. In addition, each of the primary transfer rollers 5Y, 5M, 5C, and 5K is connected to a bias power supply (not shown) for applying a primary transfer bias. Each bias power supply changes the transfer bias applied to each primary transfer roller by control of a control unit (not shown).
[0217] Next, the operation of forming a yellow image in the first unit 10Y will be described.
[0218] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.
[0219] The photoreceptor 1Y has a conductivity (e.g., a volume resistivity of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ωcm or less. The photosensitive layer generally has a high resistance (the resistance of a common resin), but has a property that the resistivity of the portion irradiated with the laser beam changes when the laser beam is irradiated. Therefore, according to the yellow image data sent from the control unit (not shown), the laser beam 3Y is output to the charged surface of the photoreceptor 1Y by the exposure device 3. The laser beam 3Y is irradiated to the photosensitive layer on the surface of the photoreceptor 1Y, thereby forming an electrostatic image of a yellow image pattern on the surface of the photoreceptor 1Y.
[0220] The electrostatic image is an image formed on the surface of the photoreceptor 1Y by charging, which is a so-called negative latent image. The negative latent image is formed as follows: the resistivity of the irradiated portion of the photosensitive layer is reduced by using the laser beam 3Y, so that the charged charge on the surface of the photoreceptor 1Y flows; on the other hand, the charge of the portion not irradiated with the laser beam 3Y remains, thereby forming the negative latent image.
[0221] The electrostatic image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y runs, and at the development position, the electrostatic image on the photoreceptor 1Y is visualized (developed) as a toner image by the developing device 4Y.
[0222] The developing device 4Y stores an electrostatic image developer containing, for example, at least a yellow toner and a carrier. The yellow toner is frictionally charged by being stirred inside the developing device 4Y, and has a charge of the same polarity (negative polarity) as the charge charged on the photoreceptor 1Y, and is held on the developer roller (an example of a developer holding member). After that, the surface of the photoreceptor 1Y passes through the developing device 4Y, whereby the yellow toner is electrostatically attached to the latent image portion on the surface of the photoreceptor 1Y that has been de-charged, and the latent image is developed using the yellow toner. The photoreceptor 1Y formed with the yellow toner image continues to run at a preset speed, and the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.
[0223] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y, and the electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, so that the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control section (not shown) in the first unit 10Y.
[0224] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.
[0225] In addition, the primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled in accordance with the first unit.
[0226] In this way, the intermediate transfer belt 20 to which the yellow toner image has been transferred by the first unit 10Y is sequentially conveyed through the second to fourth units 10M, 10C, and 10K, so that the toner images of the respective colors are multi-transferred in a superimposed manner.
[0227] The intermediate transfer belt 20 to which the toner images of four colors have been multi-transferred by the first to fourth units arrives at the secondary transfer section, which is composed of the intermediate transfer belt 20, the support roller 24 in contact with the inner surface of the intermediate transfer belt, and the secondary transfer roller (an example of the secondary transfer mechanism) 26 arranged on the image holding surface side of the intermediate transfer belt 20. On the other hand, the recording paper (an example of the recording medium) P is fed to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 by the feeding member at a preset timing, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has the same (-) polarity as the polarity (-) of the toner, and the electrostatic force from the intermediate transfer belt 20 to the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. It should be noted that the secondary transfer bias at this time is determined based on the resistance detected by the resistance detection mechanism (not shown) that detects the resistance of the secondary transfer section, and the voltage is controlled.
[0228] Thereafter, the recording paper P is fed into a pressure-contact portion (nip portion) of a pair of fixing rollers in a fixing device (an example of a fixing mechanism) 28 , and the toner image is fixed on the recording paper P to form a fixed image.
[0229] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copiers, printers, etc. Examples of the recording medium include, in addition to the recording paper P, OHP transparent films, etc.
[0230] In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is preferably smooth. For example, coated paper obtained by coating the surface of ordinary paper with a resin or the like, art paper for printing, etc. are preferably used.
[0231] The recording paper P on which the color image has been fixed is sent to the discharge portion, and a series of color image forming operations are completed.
[0232] <Process Cartridge / Toner Cartridge>
[0233] The process cartridge according to this embodiment will be described.
[0234] The process cartridge of this embodiment is a process cartridge that is detachably mounted in an image forming apparatus and includes a developing mechanism that stores the electrostatic image developer of this embodiment and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer.
[0235] It should be noted that the processing box of this embodiment is not limited to the above-mentioned structure, and can also be a structure including a developing device and at least one other mechanism selected from, for example, an image holding body, a charging mechanism, an electrostatic image forming mechanism, and a transfer mechanism as needed.
[0236] An example of the process cartridge according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the description of other parts is omitted.
[0237] Figure 2 1 is a schematic diagram showing the structure of the process cartridge according to the present embodiment.
[0238] Figure 2 The processing box 200 shown is constructed by, for example, integrally combining and retaining a photosensitive body 107 (an example of an image holding body) and a charging roller 108 (an example of a charging mechanism) provided around the photosensitive body 107, a developing device 111 (an example of a developing mechanism), and a photosensitive body cleaning device 113 (an example of a cleaning mechanism) through a shell 117 having a mounting guide 116 and an opening 118 for exposure to form an ink cartridge.
[0239] It should be noted that Figure 2 109 denotes an exposure device (an example of an electrostatic image forming mechanism), 112 denotes a transfer device (an example of a transfer mechanism), 115 denotes a fixing device (an example of a fixing mechanism), and 300 denotes recording paper (an example of a recording medium).
[0240] Next, the toner cartridge according to the present embodiment will be described.
[0241] The toner cartridge of the present embodiment stores the toner of the present embodiment and is attached to and detached from the image forming apparatus. The toner cartridge stores replenishment toner to be supplied to a developing mechanism provided in the image forming apparatus.
[0242] It should be noted that Figure 1 The image forming apparatus shown is an image forming apparatus having a structure of attaching and detaching toner cartridges 8Y, 8M, 8C, and 8K, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) by toner supply pipes not shown. In addition, when the toner stored in the toner cartridge is insufficient, the toner cartridge is replaced.
[0243] [Example]
[0244] The present embodiment will be described in more detail below with reference to Examples and Comparative Examples, but the present embodiment is not limited to these Examples. In addition, "parts" and "%" are based on mass unless otherwise specified.
[0245] <Production of Toner Particles>
[0246] (Toner particles (1))
[0247] -Preparation of polyester resin dispersion-
[0248]
[0249] The above monomers were added to a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was stirred, 1.2 parts of dibutyltin oxide was added. The temperature was raised from this temperature to 240°C over 6 hours while distilling off the generated water, and a dehydration condensation reaction was further continued at 240°C for 4 hours to obtain a polyester resin A having an acid value of 9.4 mgKOH / g, a weight average molecular weight of 13,000, and a glass transition temperature of 62°C.
[0250] Next, the polyester resin A was kept in a molten state and conveyed to Cavitron CD1010 (manufactured by Eurotec Co., Ltd.) at a rate of 100 parts per minute. A 0.37% dilute ammonia water prepared by diluting the reagent ammonia water with ion exchange water was added to a separately prepared aqueous medium tank, and while being heated to 120° C. by a heat exchanger, it was conveyed to the Cavitron at a rate of 0.1 liter per minute together with the above polyester resin melt. The rotor was rotated at a speed of 60 Hz and the pressure was 5 kg / cm 2 The Cavitron was operated under the conditions of , and an amorphous polyester resin dispersion in which resin particles having a volume average particle size of 160 nm, a solid content of 30%, a glass transition temperature of 62° C., and a weight average molecular weight Mw of 13,000 were dispersed was obtained.
[0251] -Preparation of Colorant Particle Dispersion-
[0252] · Cyan pigment [Pigment Blue 15:3, manufactured by Dainichi Seika Industries, Ltd.] 10 parts
[0253] · Anionic surfactant [NEOGEN SC, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.] 2 parts
[0254] 80 parts of ion exchange water
[0255] The above components were mixed and dispersed for 1 hour using a high-pressure impact disperser Ultimaizer [HJP30006, manufactured by Sugino Machine Co., Ltd.] to obtain a colorant particle dispersion having a volume average particle diameter of 180 nm and a solid content of 20%.
[0256] -Preparation of release agent particle dispersion-
[0257] · Paraffin wax [HNP 9, manufactured by Nippon Seiro Co., Ltd.] 50 parts
[0258] · Anionic surfactant [NEOGEN SC, Daiichi Kogyo Seiyaku] 2 parts
[0259] 200 parts of ion exchange water
[0260] The above components were heated to 120° C., fully mixed and dispersed using ULTRA-TURRAXT50 manufactured by IKA, and then dispersed using a pressure discharge homogenizer to obtain a release agent particle dispersion having a volume average particle size of 200 nm and a solid content of 20%.
[0261] -Production of toner particles-
[0262]
[0263] The above components were placed in a stainless steel flask, fully mixed and dispersed using ULTRA-TURRAX manufactured by IKA, and then heated to 48° C. in a heating oil bath with stirring. After maintaining at 48° C. for 30 minutes, 70 parts of the same polyester resin dispersion as above were slowly added.
[0264] After that, the pH in the system was adjusted to 8.0 using a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L, the stainless steel flask was sealed, the sealing of the stirring shaft was made a magnetic seal, and the stirring was continued while heating to 90°C and maintained for 3 hours. After the reaction was completed, the temperature was cooled at a rate of 2°C / min, filtered and fully washed with ion exchange water, and then solid-liquid separation was performed by Buchner funnel suction filtration. It was further redispersed using 3L of ion exchange water at 30°C, and stirred and washed at 300 rpm for 15 minutes. The washing operation was further repeated 6 times, and after the pH of the filtrate was 7.54 and the conductivity reached 6.5μS / cm, solid-liquid separation was performed by Buchner funnel suction filtration using No.5A filter paper. Then, vacuum drying was continued for 12 hours to obtain toner particles (1).
[0265] The volume average particle diameter D50v of the toner particles (1) is 5.8 μm.
[0266] <Production of external additives>
[0267] (Production of Abrasive Grains (Ab1))
[0268] After adding strontium chloride in an equal molar amount to titanium oxide to the metatitanic acid slurry, carbon dioxide in an amount twice the molar amount of titanium oxide was blown in at a flow rate of 1 L / min, and ammonia water was added at the same time. The pH value at this time was 8. After washing the precipitate with water, it was dried at 110°C for 24 hours, then sintered at 800°C, mechanically crushed, and classified to produce abrasive particles (Ab1) composed of strontium titanate particles. The number average particle size of the obtained abrasive particles (Ab1) is as follows.
[0269] Abrasive particles (Ab1): strontium titanate particles (average particle size 0.12 μm)
[0270] (Production of Titanium Dioxide Particles (A2 to A5, B2 to B5))
[0271] -Titanium dioxide particles (A2)-
[0272] First, the wet sedimentation method (dissolving ilmenite in sulfuric acid, separating iron powder, and TiOSO 4 Hydrolysis to form TiO(OH) 2 ) to produce TiO(OH) 2 It should be noted that in TiO(OH) 2 During the manufacturing process, dispersion adjustment and water washing are performed for hydrolysis and nucleation. The obtained TiO(OH) 2 100 parts of the product were dispersed in 1000 parts of water, and 20 parts of isobutyltrimethoxysilane were added dropwise thereto while stirring at room temperature (25°C). The product was then filtered and repeatedly washed with water. After that, the metatitanic acid, which had been subjected to surface hydrophobic treatment with isobutyltrimethoxysilane, was dried at 130°C to produce a product having a volume average particle size of 20 nm and a BET specific surface area of 132 m 2 / g, titanium dioxide particles (A2) with a specific gravity of 3.4.
[0273] -Titanium dioxide particles (A3)-
[0274] Titanium dioxide particles (A3) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 160°C.
[0275] -Titanium dioxide particles (A4)-
[0276] Titanium dioxide particles (A4) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 100°C.
[0277] -Titanium dioxide particles (A5)-
[0278] Titanium dioxide particles (A5) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 200°C.
[0279] -Titanium dioxide particles (B2)-
[0280] Titanium dioxide particles (B2) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 400°C.
[0281] -Titanium dioxide particles (B3)-
[0282] Titanium dioxide particles (B3) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 600°C.
[0283] -Titanium dioxide particles (B4)-
[0284] Titanium dioxide particles (B4) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 350°C.
[0285] -Titanium dioxide particles (B5)-
[0286] Titanium dioxide particles (B5) were obtained in the same manner as in the titanium dioxide particles (A2) except that the metatitanic acid subjected to a surface hydrophobization treatment with isobutyltrimethoxysilane was dried at 700°C.
[0287] <Preparation of carrier>
[0288] 14 parts of toluene, 2 parts of styrene-methyl methacrylate copolymer (polymerization mass ratio 90:10, weight average molecular weight 80,000) and 0.2 parts of carbon black (R330 manufactured by Cabot Corporation) were mixed and stirred for 10 minutes using a stirrer to prepare a dispersion. Next, the dispersion and 100 parts of ferrite particles (volume average particle size 36 μm) were charged into a vacuum degassing kneader, stirred at 60° C. for 30 minutes, and then degassed under reduced pressure under heating to dry the mixture to obtain a carrier.
[0289] <Preparation of external carrier (C1)>
[0290] 0.05 parts of titanium dioxide particles (B1) as titanium dioxide particles (B) were added to 100 parts of the carrier, the mixture was placed in a V-type blender, stirred at 40 rpm for 20 minutes, and then passed through a sieve with a mesh size of 75 μm to prepare an externally added carrier (C1).
[0291] <Preparation of external carriers (C2) to (C5)>
[0292] Externally added carriers (C2) to (C5) were obtained in the same manner as the externally added carrier (C1) except that the type and amount of the titanium dioxide particles (B) were changed to the type and amount described in Table 1.
[0293] <Preparation of Toner (T1)>
[0294] To 100 parts of the toner particles (1), 1 part of titanium dioxide particles (A1) as titanium dioxide particles (A), 0.04 parts of fatty acid metal salt particles (FM1), 0.04 parts of abrasive particles (Ab1) and 2.0 parts of silica particles (A200 manufactured by Aerosil) are added, and the mixture is blended at a peripheral speed of 30 m / s for 15 minutes using a Henschel mixer, and then coarse particles are removed using a sieve with a mesh size of 45 μm to obtain a toner (T1).
[0295] <Preparation of Toners (T2) to (T11)>
[0296] Toners (T2) to (T11) were obtained in the same manner as in Toner (T1) except that the types and addition amounts of the titanium dioxide particles (A), the fatty acid metal salt particles, and the abrasive particles were changed to those shown in Table 2.
[0297] <Example 1>
[0298] Then, the obtained toner (T1) and the external carrier (C1) were charged into a V-type blender at a ratio of toner:external carrier=5:95 (mass ratio), and stirred for 20 minutes to obtain a developer (1).
[0299] <Examples 2 to 19, Comparative Example 1>
[0300] A developer was obtained in the same manner as in Example 1 except that the types of toner and external carrier were changed as shown in Table 3.
[0301] <Evaluation>
[0302] Using the developer obtained in each example, image density unevenness was evaluated. The results are shown in Table 3.
[0303] (Evaluation of image density unevenness)
[0304] Evaluation of image density unevenness was performed as follows.
[0305] The obtained developer was filled into the developing device of the image forming device "DocuCentre Color 450CP (manufactured by Fuji Xerox Co., Ltd.)" which was adjusted in a manner capable of developing using a positively charged toner, and was placed in a high temperature and high humidity environment (28°C, 85% RH) for one night, and then placed in a low temperature and low humidity environment (10°C, 15% RH) for one night.
[0306] Subsequently, 10,000 images with an image density of 2.5% were output in a low temperature and low humidity environment (10°C, 15% RH), and then images with an image density of 80% were output. The image density at 5 locations in the image was measured using X-rite938 (manufactured by X-rite), and the average image density and standard deviation were calculated.
[0307] The evaluation criteria are as follows.
[0308] -Evaluation Criteria-
[0309] A: Standard deviation ≤ 0.1
[0310] B: 0.1<Standard Deviation ≦0.3
[0311] C: 0.3<Standard Deviation ≦ 0.5
[0312] D: 0.5<Standard Deviation ≦ 0.7
[0313] The details of the titanium dioxide particles (A) described in Table 2 are as follows.
[0314] Titanium dioxide particles (A1): STT100H, TAYCA Co., Ltd., refractive index 2.2, crystallite diameter 14 nm, number average particle diameter 0.02 μm
[0315] Titanium dioxide particles (A2): Titanium dioxide particles (trade name, etc.) prepared by firing at 130°C, refractive index 2.1, crystallite diameter 13 nm, number average particle diameter 0.02 μm
[0316] Titanium dioxide particles (A3): Titanium dioxide particles prepared by firing at 160°C, refractive index 2.3, crystallite diameter 15 nm, number average particle diameter 0.02 μm
[0317] Titanium dioxide particles (A4): Titanium dioxide particles prepared by firing at 100°C, refractive index 2.0, crystallite diameter 12 nm, number average particle diameter 0.02 μm
[0318] Titanium dioxide particles (A5): Titanium dioxide particles prepared by firing at 200°C, refractive index 2.4, crystallite diameter 16 nm, number average particle diameter 0.02 μm
[0319] The details of the titanium dioxide particles (B), fatty acid metal salt particles, and abrasives described in Table 1 are as follows.
[0320] Titanium dioxide particles (B1): JMT2000, TAYCA Co., Ltd., refractive index 2.7, crystallite diameter 42 nm, number average particle size 0.02 μm
[0321] Titanium dioxide particles (B2): Titanium dioxide particles prepared at a firing temperature of 400°C. Refractive index 2.6, crystallite diameter 41 nm, number average particle diameter 0.02 μm
[0322] Titanium dioxide particles (B3): Titanium dioxide particles prepared by firing at 600°C, with a refractive index of 2.8, a crystallite diameter of 43 nm, and a number average particle size of 0.02 μm
[0323] Titanium dioxide particles (B4): Titanium dioxide particles prepared by firing at 350°C, with a refractive index of 2.5, a crystallite diameter of 40 nm, and a number average particle size of 0.02 μm
[0324] Titanium dioxide particles (B5): Titanium dioxide particles prepared by firing at 700°C, with a refractive index of 2.9, a crystallite diameter of 44 nm, and a number average particle size of 0.02 μm
[0325] Fatty acid metal salt particles (FM1): Mz-2 produced by NOF Corporation was classified using a curved pipe jet classifier (EJ-L-3 (LABO) produced by Nippon Iron & Steel Mining Co., Ltd.) to obtain particles having a number average particle size of 1 μm.
[0326] Fatty acid metal salt particles (FM2): Mz-2 produced by NOF Corporation was classified using a curved pipe jet classifier (EJ-L-3 (LABO) produced by Nippon Iron & Steel Mining Co., Ltd.) to obtain particles having a number average particle size of 5 μm.
[0327] Fatty acid metal salt particles (FM3): Mz-2 produced by NOF Corporation was classified using a curved pipe jet classifier (EJ-L-3 (LABO) produced by Nippon Iron & Steel Mining Co., Ltd.) to obtain particles having a number average particle size of 0.5 μm.
[0328] Fatty acid metal salt particles (FM4): Mz-2 produced by NOF Corporation was classified using a curved pipe jet classifier (EJ-L-3 (LABO) produced by Nippon Iron & Steel Co., Ltd.) to obtain particles having a number average particle size of 10 μm.
[0329] Abrasive particles (Ab1): Strontium titanate particles (average particle size 1.0 μm)
[0330] Abrasive particles (Ab2): Strontium titanate particles (average particle size 5.0 μm)
[0331] Abrasive particles (Ab3): strontium titanate particles (average particle size 0.5 μm)
[0332] "Polarity" indicates the sign of the surface potential of the fatty acid metal salt particles.
[0333] “-” in the toner type (T7) indicates that fatty acid metal salt particles and abrasive are not contained.
[0334] "(A) / (B)×100" described in Table 3 represents the mass % of the content of the titanium dioxide particles (A) relative to the content of the titanium dioxide particles (B) in the electrostatic image developer.
[0335] "(FM) / (A)×100" described in Table 3 represents the mass % of the fatty acid metal salt particle content relative to the titanium dioxide particle (A) content.
[0336] "(Ab) / (A)×100" in Table 3 represents the mass % of the abrasive content relative to the content of the titanium dioxide particles (A).
[0337]
[0338]
[0339]
[0340] As can be seen from the above results, in this embodiment, the unevenness in image density generated when high-density images are repeatedly formed is suppressed compared to the comparative example.
Claims
1. An electrostatic image developer comprising: a toner including toner particles, vector, and An external additive comprising fatty acid metal salt particles, an abrasive and two types of titanium dioxide particles having different refractive indices, The two types of titanium dioxide particles having different refractive indices are titanium dioxide particles (A) attached to the toner particles and titanium dioxide particles (B) attached to the carrier. The content of the titanium dioxide particles (A) is 0.1% by mass or more and 50% by mass or less relative to the content of the titanium dioxide particles (B). The refractive index of the titanium dioxide particles (A) is greater than or equal to 2.0 and less than 2.4, The refractive index of the titanium dioxide particles (B) is 2.4 or more and 2.8 or less.
2. The electrostatic image developer according to claim 1, wherein The fatty acid metal salt particles are fatty acid zinc particles. The abrasive is titanate metal salt particles.
3. The electrostatic image developer according to claim 2, wherein The fatty acid metal salt particles are zinc stearate particles. The abrasive is strontium titanate particles.
4. The electrostatic image developer according to any one of claims 1 to 3, wherein The content of the fatty acid metal salt particles is 1% by mass or more and 10% by mass or less relative to the content of the titanium dioxide particles (A).
5. The electrostatic image developer according to any one of claims 1 to 3, wherein The content of the polishing agent is 1% by mass or more and 10% by mass or less relative to the content of the titanium dioxide particles (A).
6. An electrostatic image developer comprising: a toner including toner particles, vector, and An external additive comprising fatty acid metal salt particles, an abrasive and two types of titanium dioxide particles having different crystallite diameters, The two types of titanium dioxide particles having different crystallite diameters are titanium dioxide particles (A) attached to the toner particles and titanium dioxide particles (B) attached to the carrier. The content of the titanium dioxide particles (A) is 0.1% by mass or more and 50% by mass or less relative to the content of the titanium dioxide particles (B). The crystallite diameter of the titanium dioxide particles (A) is greater than 12 nm and less than 16 nm. The titanium dioxide particles (B) have a crystallite diameter of 40 nm to 44 nm.
7. A process cartridge detachably mounted in an image forming apparatus, comprising a developing mechanism storing the electrostatic image developer according to any one of claims 1 to 6, and developing an electrostatic image formed on a surface of an image holding member into a toner image using the electrostatic image developer.
8. An image forming apparatus comprising: Image holding body; A charging mechanism for charging the surface of the image holding body; An electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holding member; a developing mechanism storing the electrostatic image developer according to any one of claims 1 to 6, and developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer; A transfer mechanism for transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; as well as The fixing mechanism fixes the toner image transferred to the surface of the recording medium.
9. An image forming method comprising the following steps: A charging step of charging the surface of the image holding body; An electrostatic image forming step of forming an electrostatic image on the charged surface of the image holding member; a developing step of developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer according to any one of claims 1 to 6; a transfer step of transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; as well as In the fixing step, the toner image transferred to the surface of the recording medium is fixed.
Citation Information
Patent Citations
Toner and developer for electrostatic latent image development, and image forming method
JP2005266560A
Image forming apparatus
JP2014149503A
Toner for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
JP2017146538A
Electrostatic charge image developing toner, electrostatic charge image developer, toner cartridge, developer cartridge, process cartridge, image forming method, and image forming apparatus
CN103309189A
Electrostatic charge image developing toner, electrostatic charge image developer, and toner cartridge
CN107015448A
